Ubezpieczenia na życie w gospodarstwach domowych - wybrane aspekty - Dembowska, Barbara (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
This article presents an analysis of having life insurance products in Polish households. There are used the results of research made from Central Statistical Office in Poland in 1998 and 2004. The analysis pointed increase number of individual life insurance products and decrease number of group life insurance products in Polish households in this period. This paper presents, that the main reason of buying life insurance products is anxiety of the future also. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 1, s. 131-137